An ohmic heating system for pasteurizing fluid medium. - Mariun, Norman; Jamaludin, Hisamuddin; Jamaludin, Nurul Faezawaty; Hizam, Hashim (2011)

(untitled)
The present invention provides a supercritical fluid extraction (SFE) process for extracting oil of kenaf seed (Hibiscus cannabinus L.), wherein the SFE process utilises a supercritical fluid and is conducted in a pressure rsnging from 200 to 600 bars with a temperature ranging from 40 to 80C.